Investigation of solid particle erosion behaviour of Fe-Cr alloy coating. (1st February 2023) - Sharma, Ratnesh Kumar; Das, Randip Kumar; Kumar, Shiv Ranjan
The purpose of present study was to examine the erosion wear behaviour of Fe-Cr coating deposited on 316 L steel using HVOF coating technology. Chromium content was varied (0-15) wt. % in the step of 5 wt. %. The erosion wear test was performed on Air Jet Erosion Tester by choosing set of parameters as per steady state condition and Taguchi Orthogonal array L16. On adding 5 wt. % Cr, the mechanical properties such as hardness and fracture toughness were improved by 21% and 47% respectively. In steady-state wear conditions, specific wear rate was increased with the increase in impact velocity and slurry concentration. Taguchi design of experiment revealed a particular set of parameter for minimum erosion wear rate such as chromium content of 15 wt. %, impact velocity of 40 m/sec, impingement angle of 45° and slurry concentration of 8 gm/litre.